1987
DOI: 10.1113/jphysiol.1987.sp016551
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and selectivity of a low‐voltage‐activated calcium current in chick and rat sensory neurones.

Abstract: SUMMARY1. Using the whole-cell recording mode of the patch-clamp technique, we have investigated kinetic and selectivity properties of a low-voltage-activated (l.v.a.) Ca2+ current in chick and rat dorsal root ganglion (d.r.g.) neurones.2. L.v.a currents were activated at about -50 mV and reached maximum amplitudes between -30 and -20 mV with averages of -0-16 nA in chick and -03 nA in rat d.r.g. cells with 5 mM-extracellular Ca2+. Between -60 and -20 mV, the time to peak, tp, of this current decreased with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
222
4
3

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(267 citation statements)
references
References 45 publications
38
222
4
3
Order By: Relevance
“…The current density oflCa L of 15 pA/pF in 10 mM Ca was smaller than the current density measured in Necturus taste cells (32 pA/pF in 10 mM Ca; or in adrenal chromaffin cells (33 pA/pF in 5 mM Ca; Fenwick et al, 1982b) but similar to the density found in pancreatic /3 cells (12 pA/pF in 10 mM Ca; Rorsman and Trube, 1986). /Ca T represented only 25% of the current density of/Ca L (measured in Ca), a value typically observed for other cells (Bossu et al, 1985;Fedulova et al, 1985;Carbone and Lux, 1987;Fox et al, 1987).…”
Section: Two Types Of Ca Currentsmentioning
confidence: 78%
“…The current density oflCa L of 15 pA/pF in 10 mM Ca was smaller than the current density measured in Necturus taste cells (32 pA/pF in 10 mM Ca; or in adrenal chromaffin cells (33 pA/pF in 5 mM Ca; Fenwick et al, 1982b) but similar to the density found in pancreatic /3 cells (12 pA/pF in 10 mM Ca; Rorsman and Trube, 1986). /Ca T represented only 25% of the current density of/Ca L (measured in Ca), a value typically observed for other cells (Bossu et al, 1985;Fedulova et al, 1985;Carbone and Lux, 1987;Fox et al, 1987).…”
Section: Two Types Of Ca Currentsmentioning
confidence: 78%
“…48 An important calcium current with properties well suited to control excitability is the low-voltageactivated (LVA) current. 5,16 Until now, this current could not be detected in dissociated neurons of adult animals. We showed recently 21 that the in situ patchclamp technique in the slice allows the detection of LVA currents.…”
mentioning
confidence: 96%
“…These were premixed at the required concentration by diluting stock solutions in ABSS. The solutions were applied in the vicinity (about 100pm) of the recorded neurone from a multi-barrelled perfusion pipette constructed from 7 hypodermic syringe needles (Carbone & Lux, 1987 …”
Section: Electrophysiological Recordingmentioning
confidence: 99%